The effect of iron slag enriched cow manure, zeolite and pumice on the sunflower Pb uptake in a soil irrigated with wastewater of battery factory - Amir Hossein Baghaie; Raheleh Mirzaee (Shiraz University of Medical Sciences, 2019)
Introduction: In order to optimize the use of industrial wastewater, proper management practices should be applied for wastewater treatment. Thus, this study was done to evaluate the effect of iron slag enriched cow manure, zeolite and pumice on the sunflower Pb concentration in a soil irrigated with wastewater of battery factory. Methods: In this descriptive study, treatments consisted of applying iron slag (0, 1 and 2 % (W/W)) enriched cow manure at the rates of 0 and 30 t/ha, using zeolite (0 and 2 % (W/W)) and pumice (0 and 8 % (W/W), and sunflower irrigation with the wastewater of battery factory mixed with well water with the ratio of 1:1 and 1:2 (water/wastewater). After 60 days, the plant was harvested and the concentration of Pb and Fe was measured using atomic absorption spectroscopy. The SOD enzyme activity was also determined. Results: Application of 2% zeolite and 8% (W/W) pumice significantly decreased the Pb concentration of the soil irrigated with the wastewater at the ratio of 2:1 (wastewater/water) by 8.1%, respectively. The plant Pb concentration was also increased by 11.2 and 13.3%, respectively. The SOD enzyme activity showed a similar trend with the plant Pb concentration. Enrichment of cow manure with iron slag significantly decreased the Pb concentration of the plant that was irrigated with the wastewater at the ratio of 2:1 (wastewater/water) by 11.3%   Conclusion: Iron slag enriched cow manure, pumice and zeolite significantly decreased the soil and plant Pb concentration of the soil and plant that was irrigated with wastewater.